State and Education in the Planetary Geopolitical Context - Rivas, José Gregorio (2022)
The research was developed in a rural school in Lara state under the epistemological conception of heterodox Marxism and the method of the concrete totality in order to reveal the prevailing conditions in the rural educational system in the context of planetary geopolitics. Interview, documentary and participatory observation techniques were applied. Among the findings found, the following stand out: decontextualization of rural education, lack of a specific curriculum and the merging of degrees, among others. The support of the teachers was obtained to join a basic training plan to facilitate the theoretical-methodological tools that allow them to assume the responsibility of facilitating the programmatic contents of physical education. It was concluded that rural education faces challenges that must be faced with pedagogical strategies and alliances in accordance with the new times and educational policies.